Existence theory for nonlocal boundary value problems involving mixed fractional derivatives - Ahmad, Bashir; Ntouyas, K.; Alsaedi, Ahmed (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we develop the existence theory for a new kind of nonlocal three-point boundary value problems for differential equations and inclusions involving both left Caputo and right Riemann–Liouville fractional derivatives. The Banach and Krasnoselskii fixed point theorems and the Leray–Schauder nonlinear alternative are used to obtain the desired results for the singlevalued problem. The existence of solutions for the multivalued problem concerning the upper semicontinuous and Lipschitz cases is proved by applying nonlinear alternative for Kakutani maps and Covitz and Nadler fixed point theorem. Examples illustrating the main results are also presented.
Keywords: fractional differential equations; fractional differential inclusion; fractional derivative; boundary value problem; existence, fixed point theorems